Droplet-Scale Conversion of Aluminum into Transparent Aluminum Oxide by Low-Voltage Anodization in an Electrowetting System - Budlayan, Marco Laurence M (Langmuir : the ACS journal of surfaces and colloids, 2025)
A localized conversion of aluminum into transparent aluminum oxide by droplet-scale anodization is demonstrated in this work. The anodized region can be contained and controlled on the basis of the electrowetting response of the droplet. A highly uniform and transparent anodized spot was achieved using an anodization voltage of 2 V for 10 min. We analyzed the chemical evolution during the formation of the transparent oxide layer using X-ray photoelectron spectroscopy, which revealed the dynamic interplay between Al(OH), AlO(OH), and Al2O3 formation and dissolution during the conversion process. The dominant presence of aluminum oxide/hydroxide on the transparent spot after anodization was observed. The morphological characteristics of the transparent oxide layer exhibited a reduction in surface roughness as anodization time increased. Additionally, the formation of randomly distributed nanopores was observed in the anodized samples. X-ray diffraction results revealed the amorphous nature of the produced transparent oxide layer. This droplet-scale anodization technique can be extended to other transparent metal oxides, providing an environmentally friendly and cost-effective fabrication route toward sustainable electronics and other related applications